Accumbal D2R-medium spiny neurons regulate aversive behaviors through PKA-Rap1 pathway. (February 2021) - Lin, You-Hsin; Yamahashi, Yukie; Kuroda, Keisuke; Faruk, Md. Omar; Zhang, Xinjian; Yamada, Kiyofumi; Yamanaka, Akihiro; Nagai, Taku; Kaibuchi, Kozo
Abstract: The nucleus accumbens (NAc) plays a crucial role in various mental activities, including positive and negative reinforcement. We previously hypothesized that a balance between dopamine (DA) and adenosine signals regulates the PKA-Rap1 pathway in medium spiny neurons expressing DA D1 receptors (D1R-MSNs) or D2 receptors (D2R-MSNs) and demonstrated that the PKA-Rap1 pathway in D1R-MSNs is responsible for positive reinforcement. Here, we show the role of the PKA-Rap1 pathway in accumbal D2R-MSNs in negative reinforcement. Mice were exposed to electric foot shock as an aversive stimulus. We monitored the phosphorylation level of Rap1gap S563, which leads to the activation of Rap1. Electric foot shocks increased the phosphorylation level of GluN1 S897 and Rap1gap S563 in the NAc. The aversive stimulus-evoked phosphorylation of Rap1gap S563 was detected in accumbal D2R-MSNs and inhibited by pretreatment with adenosine A2a receptor (A2aR) antagonist. A2aR antagonist-treated mice showed impaired aversive memory in passive avoidance tests. AAV-mediated inhibition of PKA, Rap1, or MEK1 in accumbal D2R-MSNs impaired aversive memory in passive avoidance tests, whereas activation of this pathway potentiated aversive memory. Optogenetic inactivation of mesolimbic DAergic neurons induced place aversion in real-time place aversion tests. Aversive response was attenuated by inhibition of PKA-Rap1 signaling in accumbal D2R-MSNs. These results suggested that accumbal D2R-MSNs regulate aversive behaviors through the A2aR-PKA-Rap1-MEK pathway. Our findings provide a novel molecular mechanism for regulating negative reinforcement. Highlights: Electric foot shocks promoted the phosphorylation of Rap1gap in accumbal D2R-MSNs. A2aR antagonist inhibited electric foot shock-evoked Rap1gap phosphorylation. Inhibition of Rap1 pathway in accumbal D2R-MSNs impaired aversive behaviors. Accumbal D2R-MSNs regulate aversive behaviors through the A2aR-PKA-Rap1 pathway.